TEKNIK PEMODELAN 3D CITRA SATELIT LAPAN TUBSAT DENGAN VIDEOGRAMMETRI (Studi Kasus: Gunung Semeru) - Atriyon Julzarika (Widyariset, 2010)
LAPAN TUBSAT imagery can be made in 3D model using Videogrammetry. These 3D model used stereo model concept, geodetic control network, and Kriging method. First, LAPAN TUBSAT imagery in the form of video wastaken in two photo which have 60% overlay to create a stereo model. It needs to correct geometrically these two photos. After making 3D model, then geodetic control network that has been made can get ground control points from SRTM30. Kriging method that was resulted from geodetic control network was useful for making 3D model. 3D model needs statistical tests, they are display (athwart profile) and also geo-statisticsl. Its vertical accuracy was 5–9 m for SRTM30 with range 26–35 m. The research result concluded that LAPAN TUBSAT 3D model was created by Videogrammetry.